Praise this [videorecording (DVD)] - Chism, Tina Gordon; Broussard, Brandon; Obayuwana, Hudson; Savage, Jana; Bailey, Chloe, 1998-; Wilds, Tristan, 1989-; Druski; Baker, Birgundi; Washington, Anjelika; Quavo, 1991- (Universal, 2023)
Set in the world of Atlanta's competitive gospel youth choir praise teams, five-time Grammyʼ nominee Chloe Bailey stars as Sam, a young woman with dreams of becoming music's next big superstar. But her plans take an unexpected detour when she is forced to join her cousin's struggling praise team in the lead-up to a national competition. Get ready for an uplifting good time with this music-filled comedy that will fill your heart with praise!